Casanova Was A Book Lover : And Other Naked Truths and Provocative Curiosities about the Writing, Selling, and Reading of Books - Hamilton, John Maxwell (Book collections on Project MUSE., 2000)
Everyone knows which books people buy; they can just look at the best-seller lists. But who knows which books people steal? Who, for that matter, knows that authors ruin the book market by writing too much? Or why book critics are not critical? Or why librarians need to throw out more books? Who, indeed, knows the answer to that all-important question in our democracy: should presidents and presidential candidates write books? (The answer is no.) In this irreverent analysis of the book industry, John Maxwell Hamilton a longtime journalist and public radio commentator answers these question.